Citrus Cold Weather Protection and Irrigation Scheduling Tools Using Florida Automated Weather Network (FAWN) Data - John L. Jackson; Kelly Morgan; William R. Lusher (EDIS, 2009)
SL-296, an 8-page illustrated fact sheet by John L. Jackson, Kelly Morgan, and William R. Lusher, provides an overview of the water saving tools that are available to citrus growers on the FAWN Web site — the Cold Protection Toolkit and the citrus microsprinkler irrigation scheduler. Published by the UF Department of Soil and Water Sciences, September 2009.